Simulating a WSN-Based Wildfire Fighting Support System - Garcia, E.M.; Serna, M.A.; Bermudez, A.; Casado, R. (2008 IEEE International Symposium on Parallel and Distributed Processing with Applications, 2008)
This paper presents the simulation environment for the EIDOS (equipment destined for orientation and safety) architecture applied to wildfire fighting operations. The development of this environment involves a multidisciplinary study, in which we have to handle several different types of information (geographical data, vegetation models, fire models, etc.) and devices (sensors, aerial vehicles, and mobile devices). Therefore, the simulation tool is actually composed of several independent and interconnected modules.